Monitoring organizational Article Processing Charges (APCs) using external sources: Turku University Library case - Linna, Anna-Kaarina; Ylönen, Irene; Salmi, Anna (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2023)
As open access publishing has become more widespread and required by research funders and the research community, the management and monitoring of article processing charges (APCs) have emerged as an important task in research organisations around the world. Within this tendency, a question of the comprehensiveness of organisational APC monitoring has become relevant. This case study demonstrates how the comprehensiveness of in-house APC monitoring can be evaluated using international bibliographic information sources like Web of Science and Scopus, where it is possible to identify the corresponding author, as well as Unpaywall and DOAJ, which contain information about the open access statuses and APCs of articles. Based on study results, it can be assumed that the organisation’s in-house bookkeeping has succeeded in registering 52 percent of APC invoices while 48 percent have not been identified. The results show that the number of unreported publications that have been openly published and whose corresponding author is affiliated with the university is almost equal to those registered in the university’s institutional APC report. The study describes the stages of data collection and processing in order of implementation, which allows a similar review to be feasible in another organisation. At the end of the article, development proposals are presented for both the organisations’ in-house data collection and the content of publishers’ invoices.